Low Molecular Weight Fucoidan Inhibits Pulmonary Fibrosis In Vivo and In Vitro via Antioxidant Activity. (2nd March 2022) - Dong, Huidan; Xue, Tao; Liu, Yanjuan; He, Shan; Yi, Yanliang; Zhang, Bo; Xin, Jie; Wang, Zhen; Li, Xinpeng
Abstract : In this study, sulfated polysaccharides extracted from Laminaria japonica were degraded by free radicals to obtain low molecular weight fucoidan (LMWF). The in vivo and in vitro effects of LMWF on bleomycin-treated pulmonary fibrosis mice and TGF-treated A549 cells, respectively, were evaluated, and the role of antioxidant activity was assessed. H&E, Masson's trichrome, and Sirius red staining results showed that bleomycin induced obvious pathological changes and collagen deposition in the lung tissue of mice. However, LMWF effectively inhibited collagen deposition, and based on immunohistochemistry analyses, LMWF can also inhibit the expression of fibrosis markers. At the same time, LMWF could regulate related antioxidant factors in the lung tissue of pulmonary fibrosis mice and reduce the pressure of oxidative stress. Moreover, LMWF could improve the morphology of cells induced with TGF, which confirmed that LMWF could inhibit fibrosis via antioxidant activity modulation.